Surgical specimen histology revealed inadequacy of conventional transbronchial needle aspiration sample in the diagnosis of adenosquamous lung carcinoma - Chen, Jing; Gao, Ya-Dong; Cao, Yan; Yang, Jiong; Luo, Guang-Wei (Journal of Thoracic Disease; Vol 7, No 4 (April 28, 2015): Journal of Thoracic Disease, 2015)
Objective: We retrospectively reviewed the accuracy of conventional transbronchial needle aspiration (cTBNA) in the subtyping of lesions located in or around central airways by comparing the histological diagnosis based on TBNA and surgical specimens. Materials and methods: cTBNA was conducted in consecutive patients with lesions located in or around the central airways (trachea, left and right primary bronchi, hilar and mediastinal masses or lymph nodes) between October 2012 and May 2014 in Wuhan No. 1 Hospital. The aspirated specimens in all patients were performed cytological and/or histopathological examination. Of these patients, some were subjected to surgical resection and histopathological examination was performed by the Department of Pathology. In the patients with gross specimens, the final diagnosis was established based on histopathological results from these specimens. Results: In 63 patients diagnosed with cTBNA for the lesions located in or around the central airways, 23 patients with a diagnosis of lung cancer or atypical hyperplasia underwent surgery. The final diagnosis based on histopathology of surgery specimen was lung cancer in 22 patients [3 small cell lung cancer (SCLC), 9 squamous cell carcinoma (SCC), 5 adenocarcinoma (ADC), 4 adenosquamous carcinoma (ADS) and 1 neuroendocrine carcinoma], and inflammatory pseudotumor in 1 patient. The overall diagnostic yield of cTBNA for lung cancer was 95.7% (22/23), but the accuracy for histological typing of lung cancer is only 63.6% (14/22), for adenosquamous lung carcinoma was only 25% (1/4). Conclusions: cTBNA is a safe and effective procedure that can be used for the diagnosis of central lung cancer. However, the accuracy of TBNA for the histological classification of lung cancer is relatively low, especially for adenosquamous lung carcinoma.